The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.atmosenv.2020.118127
|View full text |Cite
|
Sign up to set email alerts
|

Application of Improved CFD Modeling for Prediction and Mitigation of Traffic-Related Air Pollution Hotspots in a Realistic Urban Street

Abstract: The correct prediction of air pollutants dispersed in urban areas is of paramount importance to safety, public health and a sustainable environment. Vehicular traffic is one of the main sources of nitrogen oxides (NO x ) and particulate matter (PM), strongly related to human morbidity and mortality. In this study, the pollutant level and distribution in a section of one of the main road arteries of Antwerp (Belgium, Europe) are analyzed. The assessment is performed through computational fluid dynamics (CFD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 114 publications
(178 reference statements)
0
20
0
Order By: Relevance
“…Wind catchers have been used to improve indoor air quality, however, some recent studies show that wind catchers can be effectively employed to improve outdoor air quality as well [31,32]. Located at the roof of certain buildings facing the main street, wind catchers offer a passive method of diluting the pollutant concentrations and increasing wind speed for targeted areas within urban street canyons.…”
Section: Non-porous Obstacles-building Policy Guidelines 41 Wind Catchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind catchers have been used to improve indoor air quality, however, some recent studies show that wind catchers can be effectively employed to improve outdoor air quality as well [31,32]. Located at the roof of certain buildings facing the main street, wind catchers offer a passive method of diluting the pollutant concentrations and increasing wind speed for targeted areas within urban street canyons.…”
Section: Non-porous Obstacles-building Policy Guidelines 41 Wind Catchersmentioning
confidence: 99%
“…Some studies have shown that lift-up building design can ally provide a comfortable microclimate in summer conditions, while not causing a cold stress in the winter [33]. Although the study characterised different building s such as the 'L', 'U', 'I' and the '□' shaped buildings in different orientations (Figure wind flow (at the pedestrian level) seems to be more altered due to the shape and ar ment of the core and column supports rather than the shape of the building itself [ Employment of wind catchers appear to reduce concentration levels by up to 37% in some pedestrian-level areas, by modifying the air entrainment in the street canyons resulting in a more efficient dilution process [31]. The benefits of wind catchers are that they can be targeted for specific buildings, while not taking up space within the urban canyon at street levels.…”
Section: Lift-up Buildings and Building Permeabilitymentioning
confidence: 99%
“…CFD simulation was used to optimize the circulating air volume, return air angle, and exhaust volume of the circulating system. Lauriks et al [21] used CFD to analyze the level and distribution of pollutants in a part of Antwerp's main road artery (Belgium, Europe). Erfan et al [22] investigated the influence of the crosssectional shape of a building on the diffusion of air pollutants around the isolated building.…”
Section: Previous Studiesmentioning
confidence: 99%
“…With continued growth of computational power and advances in CFD techniques, even complex models can be done on commodity hardware. Thus, CFD modeling is routinely applied in several fields of science and engineering such as chemistry, 2,3 materials, 4 fluid flow and heat transfer, 5,6 biology, 7 drug delivery, 8 semiconductors, 9 environmental engineering, 10,11 biomedical engineering, 12 and aeronautics 13…”
Section: Introductionmentioning
confidence: 99%